2021
DOI: 10.3390/bios11030070
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Hemoglobin and Methods for Its Point of Care Testing

Abstract: Glycated hemoglobin (HbA1c) is a product of the spontaneous reaction between hemoglobin and elevated glucose levels in the blood. It is included among the so-called advanced glycation end products, of which is the most important for the clinical diagnosis of diabetes mellitus, and it can serve as an alternative to glycemia measurement. Compared to the diagnosis of diabetes mellitus by glycemia, the HbA1c level is less influenced by a short-term problem with diabetes compensation. Mass spectroscopy and chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…Currently, a wide range of nanomaterials, such as gold, silver, carbon nanotubes, graphene, and metal oxides, have been successfully applied in biosensors [87]. These materials have excellent properties, such as high biocompatibility, good water dispersibility, and large surface areas [88][89][90]. Doping nanoparticles into normal materials or substrates can improve the resulting electrochemical properties [91].…”
Section: Fao Typementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a wide range of nanomaterials, such as gold, silver, carbon nanotubes, graphene, and metal oxides, have been successfully applied in biosensors [87]. These materials have excellent properties, such as high biocompatibility, good water dispersibility, and large surface areas [88][89][90]. Doping nanoparticles into normal materials or substrates can improve the resulting electrochemical properties [91].…”
Section: Fao Typementioning
confidence: 99%
“…For the FAO-and FPOX-based sensors, graphene, AuNPs, core-shell magnetic nanoparticles, metal oxide nanolayers, and nanotubes are the common materials used as electrodes. Using novel nanomaterials as sensing and conduction materials, electrochemical sensors were developed and are expected to provide more convenient, accurate and reliable platforms for the diagnosis of diabetes in the future [88][89][90][114][115][116]. In the MIC type indirect sensors based on imprinting technology, the specific binding sites of the target molecules can be easily customized in the polymer network.…”
Section: Mic Typementioning
confidence: 99%
“…On the other hand, the blood glucose level shows the patient´s condition at the time of sampling, but does not correspond with his longterm state (35). Glycated hemoglobin, also known as HbA1c, is a form of hemoglobin created by the reaction of hemoglobin with elevated blood glucose levels by non-enzymatic glycation (45,46). According to the American Diabetes Association, the International Diabetes Federation and the World Health Organization, the diagnosis of DM is possible by an oral glucose tolerance test or by measuring HbA1c.…”
Section: Glycated Hemoglobin and Albumin Biosensorsmentioning
confidence: 99%
“…On the other hand, blood levels of HbA1c can be affected by many diseases and conditions that infl uence the lifespan of a red blood cell, for example, HbA1c decreases after a recent transfusion, blood loss, or anemia and increases during asplenia or iron-defi ciency anemia (45,47). The same glycation mechanism that acts on hemoglobin acts on other blood proteins, the most relevant of which is albumin (46). Although glycated albumin (GA) refl ects only a 2-3 weeks period of blood glucose levels, GA levels are not affected by the lifespan of red blood cells, so it can be as good a biomarker as HbA1c, which may be even better (47).…”
Section: Glycated Hemoglobin and Albumin Biosensorsmentioning
confidence: 99%
“…At this stage, the main indicators commonly used in clinical practice to detect the degree of glycemic control and the degree of abnormal glucose metabolism are glycated hemoglobin (HbA1c) and fasting blood glucose (FPG), and the application of these two indicators plays an important role in the treatment of diabetes and in the prevention and treatment of complications [ 6 ]. Uric acid is the end product of purine metabolism, and with increasing research on uric acid, it has been found to be biologically active, causing endothelial dysfunction, inflammation, vasoconstriction, and having both positive and negative antioxidant and pro-oxidant stress effects [ 7 ].…”
Section: Introductionmentioning
confidence: 99%